STUDENTS TAKING AND NOT TAKING ENGLISH PRIVATE TUTORING IN CORRELATION TO THEIR ENGLISH ACHIEVEMENTS - ANNISA DAUD (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study aims to examine students who have been in private tutoring and those who have not and its correlation English skill achievements. The research is done to fill the gap of previous studies that mainly focused on the influence of private tutoring on English communicative ability. This study used quantitative research method with questionnaire as the instrument. The data for this research are from 47 students of English department from University of Islam Malang. The data was collected through online questionnaire with the use of google form. The data is analysed using quantitative Pearson correlation to analyse the data. The finding indicated that there is a positive correlation between English private and English skills achievement, since the value is at r= 431 with the level of significance of 0.003 which indicate that the two variables are correlated. Therefore, it can be concluded that the students who have studied at English private tutoring have better score in English skills achievement than those who have not.